Contribution of natural forest products to rural livelihoods at Mavunde and Sambandou Villages, Vhembe Biosphere Reserve, South Africa - Dalu, Mwazvita T. B.; Gunter, Ashley W.; Makatu, Mulweli; Dowo, Gregory M.; Dondofema, Farai; Dalu, Tatenda (MDPI, 2022)
With ~70% of the sub-Saharan population living in rural areas, more than 90% of rural African households depend on natural forest products. Although several studies in other parts of South Africa have looked into the use of natural forest products in poverty alleviation, little is known on the roles and relative contribution of natural forest products as daily and safety nets specifically within the Vhembe Biosphere Reserve, South Africa. This study assessed the different roles played by natural forest products in households and the patterns of their relative contribution to households both as sources of income and direct consumption within differing household compositions as well as socio-economic factors. These included employment and income diversification role and the monetised value of natural resources in the rural livelihoods of households in Sambandou and Mavunde, Vhembe Biosphere Reserve, Limpopo Province, South Africa. The study inter alia compared a wide use of natural resources by two villages and determined on which forest products they most relied for their economic welfare. Their relative contributions to livelihoods were assessed by identifying factors that affected their contributions. Findings of the study showed that Sambandou had a high number of people with formal jobs and females, and fewer old-age pensioners. Differences in employment and education between villages were observed. In all villages, the most frequently used or harvested resource was fuelwood, wild edible fruits, herbs, grass/shrub hand sweepers, insects for food, thatch grass/reeds and poles for fencing and housing. Overall, Mavunde village households were found to be more dependent on natural resource harvesting both for income and subsistence substitution. Findings suggest that this may have been a consequence of socio-economic factors such as income and employment, as well as general underdevelopment in the village. This study’s findings could contribute to further studies into how these results compare to other parts of the country and region, as well as their respective developmental implications.